Inorganic salt phase change material as well as preparation method and application thereof
By adding amide temperature regulators and suitable inorganic hydrated salt components to the inorganic salt phase change material, the phase change temperature is reduced, and the problem of low energy efficiency ratio caused by high heat source temperature in the heat pump system is solved, and the heating water of the heat pump system is improved Energy efficiency.
Patent Information
- Application Number
- CN202411369844.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
In a heat pump system, the higher the phase change temperature of the phase change material, the higher the water outlet temperature, but the higher the required heat source temperature, resulting in an increase in heat transfer loss of the heat source, and the energy efficiency ratio of the heat pump system is reduced, and it is necessary to optimize heat exchange. Materials to improve the energy efficiency of heating water.
By adding a temperature regulator, such as amide compounds to the inorganic salt phase change material, and selecting appropriate inorganic hydrated salts and other components ratios, hydrogen bonds and new crystal forms are formed, phase change temperature is reduced, and phase change stability is improved. Reduce heat loss.
It realizes that while meeting the demand for effluent water temperature, reduces heat source temperature, improves the energy efficiency ratio of the heat pump system, reduces heat loss, and improves the energy efficiency of hot water.
Smart Images

Figure CN119264879A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to an inorganic salt phase change material and a preparation method and application thereof. Background Art
[0002] With the deepening of industrialization, the energy gap is becoming more and more obvious. The shortage of primary energy has attracted great attention from people. For this reason, humans have come up with many solutions. Improving energy utilization and developing renewable energy have become important issues.
[0003] Phase change energy storage is a technology that uses phase changes (solid-liquid, gas-liquid) of materials to store energy. The heating process involves two processes: sensible heat storage and latent heat storage. During the latent heat storage process, the material temperature is almost constant. Compared with water that only uses sensible heat to store heat, phase change materials have higher heat storage capacity. Therefore, phase change materials have very high application advantages in heat pump systems. For example, in the temperature range of 10°C to 65°C, the energy storage density of phase change materials is twice that of water, and the volume of the phase change module can be reduced to 50% of that of an independent water tank.
[0004] In the heat pump system, the phase change material absorbs heat from the heat source during its energy storage process, and transfers heat to low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the phase change material, the higher the outlet water temperature. However, at the same time, the required heat source temperature is also higher. The higher the temperature of the heat source, the greater the loss in the heat transfer process, and the lower the energy efficiency ratio (COP) of the heat pump system. Therefore, it is necessary to optimize the heat exchange material of the heat pump system to improve the hot water production energy efficiency of the heat pump system while meeting the outlet water temperature requirements. Summary of the invention
[0005] The embodiments of the present application provide an inorganic salt phase change material and a preparation method and application thereof, which can improve the hot water production efficiency of a heat pump system by lowering the phase change temperature of the phase change material.
[0006] In a first aspect, an embodiment of the present application provides an inorganic salt phase change material composition, the composition comprising the following components:
[0007] Inorganic hydrated salt 84.0wt.%~92.5wt.%, temperature regulator 5.5wt.%~8.0wt.%, nucleating agent 1.0wt.%~5.0wt.%, thickener 1.0wt.%~3wt.%;
[0008] Wherein, the temperature regulator is selected from at least one of amide compounds.
[0009] In some embodiments, based on the total weight of the composition, the composition includes the following components:
[0010] Inorganic hydrated salt 87.0wt.%~90.0wt.%, temperature regulator 6.0wt.%~7.0wt.%, nucleating agent 3.0wt.%~4.0wt.%, thickener 1.0wt.%~2.0wt.%.
[0011] In some embodiments, the weight ratio of the inorganic hydrated salt to the temperature regulator is S, and S ranges from 10.40 to 13.82.
[0012] In some embodiments, the inorganic hydrated salt is selected from at least one of magnesium nitrate hexahydrate, sodium thiosulfate pentahydrate, sodium acetate trihydrate, and calcium chloride hexahydrate;
[0013] The amide compound is selected from at least one of formamide, acetamide, urea and glycine;
[0014] The nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium phosphate heptahydrate, sodium pyrophosphate, sodium dihydrogen phosphate, strontium chloride hexahydrate, kainite hexahydrate, calcium sulfate dihydrate, and expanded graphite;
[0015] The thickener is selected from at least one of cyclodextrin, sodium alginate, carrageenan, pectin, sodium carboxymethyl cellulose, xanthan gum, gum arabic, and water-soluble starch.
[0016] In some embodiments, the composition further comprises a corrosion inhibitor, and the weight percentage of the corrosion inhibitor is 0.2 wt.% to 1.0 wt.% based on the total weight of the composition;
[0017] The corrosion inhibitor is selected from at least one of quaternary ammonium salt, benzotriazole, mercaptobenzimidazole and tungstate.
[0018] In some embodiments, the composition further comprises a thermally conductive filler, and the weight percentage of the thermally conductive filler is 1.5 wt.% to 3.0 wt.% based on the total weight of the composition;
[0019] The thermally conductive filler is selected from at least one of metal-organic framework, metal foam, expanded graphite, carbon nanotubes, boron nitride, molybdenum disulfide, aluminum oxide, magnesium oxide, and iron oxide.
[0020] In a second aspect, the present application provides a method for preparing an inorganic salt phase change material, comprising: mixing the components in the inorganic salt phase change material composition as described above.
[0021] In some embodiments, mixing the components of the inorganic salt phase change material composition comprises the following steps:
[0022] The inorganic hydrated salt is heated to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt, and a preheating treatment is performed to obtain a molten inorganic hydrated salt;
[0023] Adding the nucleating agent to the molten inorganic hydrated salt and performing emulsification treatment to obtain a mixture A;
[0024] Adding the thickener to the mixture A to perform thickening treatment to obtain a mixture B;
[0025] Adding the temperature regulator to the mixture B, performing a first mixing process, and obtaining a mixture C;
[0026] adding the corrosion inhibitor and the thermal conductive filler to the mixture C, performing a second mixing process, and obtaining a mixture D;
[0027] The mixture D is cooled and solidified to obtain an inorganic salt phase change material.
[0028] In some embodiments, the first mixing process includes at least a high temperature process and a low temperature process;
[0029] The high temperature treatment at least includes: a stirring speed of 150 r / min to 200 r / min, a temperature of 65° C. to 75° C., and a time of 1.5 to 2.5 h;
[0030] The low temperature treatment at least includes: a temperature of 20°C to 35°C and a time of 1h to 2h;
[0031] The total time of the first mixing treatment is 2.5 h to 4.5 h.
[0032] In some embodiments, the preheating treatment at least includes: a time of 2 hours to 3 hours, and a preheating temperature higher than the melting point of the inorganic hydrated salt in a temperature range of 18° C. to 22° C.;
[0033] The emulsification treatment at least includes: stirring at a speed of 5000 r / min to 6000 r / min for 25 min to 30 min;
[0034] The thickening treatment at least comprises: adding the thickener to the blend in batches, with a stirring speed of 30 r / min to 50 r / min, for 2 h to 3 h, and the weight of the thickener added each time is 1.0% to 2.0% of the total weight of the thickener;
[0035] The second mixing treatment at least includes: a stirring speed of 30 r / min to 50 r / min, an ultrasonic frequency of 50 kHz to 60 kHz, and a time of 1.5 h to 2 h.
[0036] In a third aspect, the present application provides an inorganic salt phase change material, which is prepared by the preparation method as described above.
[0037] In a fourth aspect, the present application provides a heat pump system, comprising an energy storage unit, wherein the energy storage unit comprises:
[0038] An energy storage shell having an energy storage cavity therein;
[0039] A heat exchange tube, disposed in the energy storage chamber; and
[0040] The phase change layer includes the inorganic salt phase change material as described above. The phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
[0041] Based on the inorganic salt phase change material and its preparation method and application in the embodiments of the present application, by adding a temperature regulator and selecting the content of each component in the inorganic salt phase change material composition to be within a suitable range, in the system of the inorganic salt phase change material of the present application, the amide compound of the temperature regulator and the inorganic hydrated salt have a strong interaction (forming hydrogen bonds), and the temperature regulator and the inorganic hydrated salt form a new crystal complex, thereby reducing the overall phase change temperature of the inorganic salt phase change material, and having good phase change stability during frequent phase changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0043] Figure 1 A method for preparing an inorganic salt phase change material according to an embodiment of the present application;
[0044] Figure 2 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application.
[0045] Reference numerals:
[0046] 10. Heat pump system; 20. Phase change layer;
[0047] 100. heat storage unit; 110. heat storage housing;
[0048] 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0049] 300, heat source; 310, outlet end; 320, inlet end; 400, heating unit;
[0050] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0051] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0052] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0053] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0054] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0055] As mentioned above, the present application provides an inorganic salt phase change material composition, which can be used to prepare an inorganic salt phase change material. The inorganic salt phase change material can be used in a heat pump system to store and release heat.
[0056] Specifically, the inorganic salt phase change material absorbs heat from the heat source during its energy storage process, and the inorganic salt phase change material transfers heat to the low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the inorganic salt phase change material, the higher the water outlet temperature. However, at the same time, the required heat source temperature is also higher. The higher the temperature of the heat source, the greater the loss in the heat transfer process, and the lower the energy efficiency ratio (COP) of the heat pump system. For example, when the temperature requirement of the heated domestic water is 40°C to 50°C, the phase change material with a phase change temperature of 58°C or 52°C is used for phase change energy storage, which can meet the temperature requirement of domestic water. When the phase change temperature of the phase change material is 58°C, a heat source of 65°C is required for phase change energy storage. When the phase change temperature of the phase change material is 52°C, only a heat source of 60°C is required for phase change energy storage. The heat loss of a heat source of 65°C is greater than that of a heat source of 60°C. Correspondingly, the energy efficiency ratio of the heat pump system using a heat source of 65°C is lower. Based on this, the present application optimizes the inorganic salt phase change material and reduces the phase change temperature of the inorganic salt phase change material, so that the heat pump system can use a low-temperature heat source, reduce heat loss, and thus improve the energy efficiency ratio of the heat pump system.
[0057] The inorganic salt phase change material composition of the present application embodiment includes the following components:
[0058] 84.0wt.% to 92.5wt.% of inorganic hydrated salt, 5.5wt.% to 8.0wt.% of temperature regulator, 1.0wt.% to 5.0wt.% of nucleating agent, 1.0wt.% to 3.0wt.% of thickener; wherein the temperature regulator is selected from at least one of amide compounds.
[0059] In the embodiments of the present application, by adding a temperature regulator and selecting the content of each component in the inorganic salt phase change material composition within a suitable range, in the system of the inorganic salt phase change material of the present application, the amide compound of the temperature regulator and the inorganic hydrated salt have a strong interaction (forming hydrogen bonds), and the temperature regulator and the inorganic hydrated salt form a new crystal complex, thereby reducing the overall phase change temperature of the inorganic salt phase change material, and having good phase change stability during frequent phase changes. Among them, the nucleating agent is used to provide nucleation sites for the inorganic hydrated salt, so that the inorganic salt phase change material can be repeatedly melted-crystallized, and then phase change energy storage is performed, and the thickener can increase the overall viscosity of the inorganic salt phase change material to inhibit the phase separation of the inorganic salt phase change material, so that the inorganic salt phase change material has good stability during frequent phase changes. When the weight percentage of the inorganic hydrated salt is lower than the lower limit of 80.0wt.%, the enthalpy of the inorganic salt phase change material decreases and the energy storage density is low. When the weight percentage of the inorganic hydrated salt is higher than the upper limit of 92.0wt.%, the proportion of other components decreases, and there is a risk of increasing supercooling and phase separation. When the weight percentage of the temperature regulator is lower than the lower limit of 4.0wt.%, the temperature regulator content is low, and the effect of reducing the phase change temperature is poor, resulting in a higher melting point of the inorganic salt phase change material. When the weight percentage of the temperature regulator is higher than the upper limit of 8.0wt.%, the temperature regulator content is high, resulting in a sharp increase in the supercooling of the inorganic salt phase change material and a deterioration of the supercooling.
[0060] In some embodiments, based on the total weight of the composition, the composition includes the following components: 87.0 wt.% to 90.0 wt.% of inorganic hydrated salt, 6.0 wt.% to 7.0 wt.% of temperature regulator, 3.0 wt.% to 4.0 wt.% of nucleating agent, and 1.0 wt.% to 2.0 wt.% of thickener. With this component, the inorganic salt phase change material has better phase change stability, more stable control of water temperature, and can further improve the hot water production energy efficiency of the heat pump system.
[0061] In some embodiments, the weight ratio of the inorganic hydrated salt to the temperature regulator is S, and the range of S is 10.40 to 13.82, which is convenient for selecting the contents of both the inorganic hydrated salt and the temperature regulator within a suitable range, so that the temperature reduction range of the temperature regulator is appropriate, thereby enabling the inorganic salt phase change material to obtain a suitable phase change temperature and the supercooling degree < 4°C.
[0062] In some embodiments, the inorganic hydrated salt is selected from at least one of magnesium nitrate hexahydrate (Ca(NO3)2·6H2O), sodium thiosulfate pentahydrate (Na2S2O3·5H2O), sodium acetate trihydrate (CH3COONa·3H2O), and calcium chloride hexahydrate (CaCl2·6H2O).
[0063] The melting point Tm of the inorganic hydrated salt is the basis for the phase change temperature of the inorganic salt phase change material. That is, in the embodiments of the present application, by adding a temperature regulator, an inorganic salt phase change material with a reduced phase change temperature based on the melting point of the inorganic hydrated salt is obtained, and it can also meet the temperature requirements of domestic water.
[0064] In some embodiments, when Tm is 58°C, the inorganic hydrated salt is selected from sodium acetate trihydrate. When 20°C < Tm ≤ 50°C, the inorganic hydrated salt is selected from at least one of sodium thiosulfate pentahydrate, sodium thiosulfate decahydrate, and calcium chloride hexahydrate.
[0065] In some embodiments, the amide compound of the temperature regulator is selected from at least one of formamide (CH3NO), acetamide (C2H5NO), urea ((NH2)2CO), and glycine. By selecting the above amide compounds as the temperature regulator, the stability of the phase change temperature of the inorganic hydrated phase change material obtained is better.
[0066] In some embodiments, the nucleating agent is selected from at least one of sodium salts, monoclinic salts, and expanded graphite. Among them, the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O), sodium pyrophosphate (Na4P2O7), sodium silicate nonahydrate (Na2SiO3·9H2O), and sodium dihydrogen phosphate. The monoclinic salts of the nucleating agent are selected from at least one of strontium chloride hexahydrate (SrCl2·6H2O), magnesium vitriol hexahydrate, and calcium sulfate dihydrate. By selecting the above nucleating agent, crystal nucleation sites can be provided for the inorganic hydrated salt, so that the inorganic salt phase change material can be repeatedly melted - crystallized, and the phase change stability is better.
[0067] Among them, when the nucleating agent is selected as an insoluble particle, in the embodiments of the present application, the particle size Dv 50 satisfies 0.84mm ≤ Dv 50 ≤ 2.0μm. In this particle size range, the nucleating agent can be uniformly dispersed in the inorganic salt phase change material to provide crystal nucleation sites for the inorganic salt phase change material.
[0068] In some embodiments, the thickener is selected from at least one of cyclodextrin, sodium alginate, carrageenan, pectin, sodium carboxymethyl cellulose, xanthan gum, gum arabic, and water-soluble starch. The above thickener has good swelling properties and can improve the viscosity of the inorganic salt phase change material, thereby improving the phase separation of the inorganic salt phase change material during the phase change process.
[0069] Since the amide bond of the amide compound can react with metal, it will cause corrosion to the container containing metal. For example, the amide compound is easy to cause corrosion to the copper container. Based on this, in some embodiments, the inorganic salt phase change material composition also includes a corrosion inhibitor, and the corrosion inhibitor is selected from at least one of molybdate, tungstate, mercaptobenzothiazole, and benzotriazole. The corrosion inhibitor can chelate with metal ions to form a chelate attached to the surface of the metal container, protect the surface of the metal container, and inhibit the corrosion of the container containing metal by the amide compound. Based on the total weight of the composition, the weight percentage of the corrosion inhibitor is 0.2wt.~1.0wt.%, and within this range, the corrosion inhibitor has a better protective effect on the container containing metal.
[0070] In some embodiments, the composition further comprises a thermally conductive filler, and the weight percentage of the thermally conductive filler is 1.5 wt.% to 3.0 wt.% based on the total weight of the composition. The thermal conductivity of the inorganic hydrated salt is relatively poor, and the inorganic salt phase change material is selected to further comprise a thermally conductive filler, which has good thermal conductivity and is used to improve the overall thermal conductivity of the inorganic salt phase change material, so as to improve the heat transfer efficiency of the inorganic salt phase change material.
[0071] The thermal conductive filler is selected from at least one of metal-organic framework, porous thermal conductive material (metal foam, expanded graphite), one-dimensional thermal conductive material (carbon nanotube), sheet thermal conductive material (boron nitride, molybdenum disulfide), and metal oxide (aluminum oxide, magnesium oxide, iron oxide). In the embodiment of the present application, the thermal conductive filler is selected from insoluble matter and exists as insoluble particles in the inorganic salt phase change material. The particle size Dv of the thermal conductive filler is 50 Satisfy 150μm≤Dv 50 ≤250μm. Within this particle size range, the components in the inorganic salt phase change material are evenly dispersed and have good stability, which prevents the local sedimentation of the thermal conductive filler, and the thermal conductive filler can play a more uniform and efficient thermal conductive role.
[0072] The present application also provides a method for preparing an inorganic salt phase change material, comprising mixing the components in the inorganic salt phase change material composition as described above to prepare the inorganic salt phase change material.
[0073] like Figure 1 As shown, in the embodiment of the present application, mixing the components of the inorganic salt phase change material composition includes the following steps:
[0074] Step S110: Heat the inorganic hydrated salt to a preheating temperature which is higher than the melting point of the inorganic hydrated salt, and perform a preheating treatment to obtain a molten inorganic hydrated salt.
[0075] Step S120: Add a nucleating agent to the molten inorganic hydrated salt and perform an emulsification treatment to obtain mixture A.
[0076] Step S130: Add a thickening agent to mixture A and perform a thickening treatment to obtain mixture B.
[0077] Step S140: Add a temperature regulator to mixture B and perform a first mixing treatment to obtain mixture C.
[0078] Step S150: Add a corrosion inhibitor and a heat conduction filler to mixture C and perform a second mixing treatment to obtain mixture D.
[0079] Step S160: Cool and solidify mixture D to form an inorganic salt phase change material.
[0080] Among them, in step S120, step S130, and step S150, the temperature can be maintained at the preheating temperature to keep the inorganic hydrated salt in a molten state so that the inorganic hydrated salt and other components are uniformly dispersed. Of course, in some embodiments of the present application, in step S110, the inorganic salt and deionized water can also be mixed according to the molar ratio of the inorganic salt and deionized water in the inorganic hydrated salt and heated to the preheating temperature for preheating treatment to obtain a molten inorganic hydrated salt.
[0081] The temperature range of the preheating temperature for the preheating treatment, which is higher than the melting point Tm of the inorganic hydrated salt, is 18°C to 22°C, so that the components in the inorganic hydrated salt composition can be uniformly mixed.
[0082] In some embodiments, the preheating treatment at least includes: the preheating temperature is 50°C to 80°C, and the time is 2h to 3h. Under this preheating condition, the inorganic hydrated salt can be fully and uniformly melted to fully and uniformly contact with other components of the inorganic salt phase change material.
[0083] In some embodiments, when the melting point Tm of the inorganic hydrated salt is 58°C, correspondingly, the preheating temperature is 80°C, and the time is 1h to 2h; when the melting point Tm of the inorganic hydrated salt is 20°C < Tm ≤ 50°C, correspondingly, the preheating temperature is 50°C to 70°C, and the time is 1.5h to 2h.
[0084] In some embodiments, the emulsification treatment at least includes: a stirring speed of 5000r / min to 6000r / min, a time of 25min to 30min, and an emulsification shearing of the molten inorganic hydrated salt and the nucleating agent under the emulsification treatment conditions through an emulsification device, so that the nucleating agent is evenly dispersed in the molten inorganic hydrated salt, so that the crystal phase integrity and dispersion uniformity of the crystals formed by the inorganic hydrated salt during the crystallization process are better.
[0085] In some embodiments, the thickening treatment at least includes: adding the thickener to the blend in batches, and stirring at a speed of 30r / min to 50r / min for 2h to 3h, and the weight of the thickener added each time is 1.0% to 2.0% of the total weight of the thickener. The thickener is added in small amounts and multiple times to facilitate the swelling of the thickener and to evenly disperse it in the inorganic salt phase change material, so as to better improve the phase separation and prevent the thickener from agglomerating and causing uneven dispersion when a large amount of thickener is added.
[0086] In the embodiment of the present application, a temperature regulator is added after the thickener. The thickener increases the viscosity of the molten inorganic hydrated salt, and can protect the amide compounds of the temperature regulator, prevent the amide compounds from decomposing, and prevent the amide compounds from becoming ineffective and failing to combine with the inorganic hydrated salt to reduce the phase change temperature of the inorganic salt phase change material.
[0087] In some embodiments, the first mixing treatment includes at least high temperature treatment and low temperature treatment in sequence, and the temperature regulator is activated by high and low temperature shock, so that the phase change temperature of the inorganic salt phase change material can be effectively reduced. The high temperature treatment includes at least: a temperature of 65°C to 75°C, a stirring speed of 150r / min to 200r / min, and a time of 1.5h to 2.5h; the low temperature treatment includes at least: a temperature of 20°C to 35°C, a time of 1h to 2h; the total time of the first mixing treatment is 2.5h to 4.5h. Under this treatment condition, the effect of the amide compound on the inorganic hydrated salt can be more fully activated to reduce the phase change temperature of the inorganic salt phase change material.
[0088] In some embodiments, the second mixing treatment includes at least: a stirring speed of 30 r / min to 50 r / min, an ultrasonic frequency of 50 kHz to 60 kHz, and a time of 1.5 h to 2 h. Under the blending treatment conditions, the corrosion inhibitor and the thermal conductive filler can be evenly dispersed in the mixture C, and the dispersion uniformity of each component in the inorganic salt phase change material composition can be further improved to prevent excessive local concentration.
[0089] In some embodiments, when the nucleating agent and the thermal conductive filler are insoluble, the nucleating agent and the thermal conductive filler are pulverized separately and then added to the corresponding mixture in the corresponding processing steps. The particle size Dv of the pulverized nucleating agent is 50Satisfy 0.84μm≤Dv 50 ≤2.0μm, particle size Dv of thermal conductive filler 50 Satisfy 150μm≤Dv 50 ≤200 μm, so that the nucleating agent and the thermal conductive filler can be evenly dispersed in the premixed liquid. The pulverization process can be carried out by at least one of a ball mill and a high-speed pulverizer.
[0090] like Figure 2 As shown, the present application also provides a heat pump system 10, which may include a water heater 100, and the water heater 100 may include an energy storage unit, the energy storage unit includes an energy storage shell 110, a heat exchange tube 200 and a phase change layer 20, and the phase change layer 20 includes the inorganic salt phase change material as described above. The energy storage shell 110 has an energy storage cavity inside, and the heat exchange tube 200 includes an inlet section, a middle section and an outlet section connected in sequence, the middle section is arranged in the energy storage cavity, and the inlet section and the outlet section extend from the energy storage cavity to the energy storage shell 110. The phase change layer 20 is filled in the energy storage cavity and coated on the middle section of the heat exchange tube 200 to exchange heat with the heat exchange medium in the heat exchange tube 200.
[0091] In some embodiments, the number of heat exchange tubes 200 of the energy storage unit is multiple. Figure 2 As shown, there are two heat exchange tubes 200, one of which is a first heat exchange tube 210 and the other is a second heat exchange tube 220. The heat pump system 10 further includes a heat source unit 300, the inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source unit 300, and the outlet section is connected to the inlet end 320 of the heat source unit 300, and the heat source unit 300 exchanges heat with the phase change layer 20 through the heat exchange medium in the first heat exchange tube 210.
[0092] The first heat exchange tube 210 and the second heat exchange tube 220 can be made of stainless steel independently. When the inorganic salt phase change material also includes a corrosion inhibitor, the first heat exchange tube 210 and the second heat exchange tube 220 can also include copper material.
[0093] like Figure 2As shown, when the water heater 100 includes an energy storage unit, the inlet section of the second heat exchange tube 220 of the energy storage unit is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The heat storage unit 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat, and the high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section Heat pipe 220, the inorganic hydrated salt transfers heat to the low-temperature water flow in the second heat exchange tube 220, and the low-temperature water flow absorbs heat and becomes high-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use; in the mixed mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and at the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220, the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and transfers the heat to the low-temperature water flow in the second heat exchange tube 220 at the same time, the low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use.
[0094] The heat pump system 10 also includes a heating unit 400, a reversing valve 500 and connecting pipes connecting the various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source 300, the second end is connected to the heating unit 400, and the third end is connected to the heat exchange pipe 200 of the heat storage unit 100. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source 300 can be connected to at least one of the heating unit 400 and the heat storage unit 100 to provide high-temperature heat exchange medium to the heating unit 400 and the heat storage unit 100 accordingly. The number of heating units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple heating units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple heating units 400, and then the heat source 300 is connected to one or more of the multiple heating units 400.
[0095] The following is a method for preparing an inorganic salt phase change material in combination with an embodiment and a comparative example. It will be understood by those skilled in the art that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following embodiments, unless otherwise specified, all raw materials used are commercially available.
[0096] In each embodiment and comparative example of the present application, the performance test method of the inorganic salt phase change material is as follows:
[0097] 1. Phase change temperature and supercooling test method
[0098] The phase change temperature is measured by the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of the inorganic hydrated salt and stabilized for 30 minutes. Then, it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ). Among them, the phase change temperature of the inorganic salt phase change material in this application is the actual phase change temperature.
[0099] Theoretical phase transition temperature (T theory ) and the actual phase transition temperature (T actual ) is the supercooling degree (T sc ).
[0100] 2. Phase change temperature reduction rate
[0101] Phase transition temperature reduction rate = (T1-T2) / T1*100%
[0102] Wherein, T1 is the phase transition temperature of the inorganic hydrated salt;
[0103] T2 is the phase change temperature of the inorganic salt phase change material.
[0104] 3. Test method for thermal enthalpy decay rate after 2000 cycles
[0105] The initial unit mass enthalpy of the phase change material is measured by DSC equipment.
[0106] The phase change material is loaded into the cycle test device and the melt-crystallization cycle is carried out according to the following steps:
[0107] (1) Initial temperature 0°C, let stand for 5 minutes;
[0108] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0109] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0110] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass thermal enthalpy of the phase change material after 2000 cycles is measured by DSC equipment.
[0111] The calculation formula of the thermal enthalpy decay rate per unit mass is: H% = (1-△H n / △H0)×100%;
[0112] Among them, △H n is the unit mass enthalpy of the phase change material after n cycles, kJ / kg;
[0113] △H0 is the initial unit mass enthalpy of the phase change material, kJ / kg.
[0114] 4. Energy storage density test method
[0115] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0116] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0117] The initial unit mass enthalpy ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0118] The energy storage density △Q is calculated according to the following formula:
[0119] △Q=р s ×(T actual -10)×C ps +(р s +р l ) / 2×△H0+р l× (65-T actual )×C pl .
[0120] Example 1-1
[0121] This embodiment provides a method for preparing an inorganic hydrated phase change material, the method comprising the following steps:
[0122] (1) Preheating
[0123] Weigh 85 g of inorganic salt sodium acetate trihydrate and heat it to a preheating temperature of 75°C to obtain molten CH3COONa·3H2O.
[0124] Based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of CH3COONa·3H2O is 85.0 wt.%.
[0125] (2) Emulsification treatment
[0126] At 75° C., 5 g of a nucleating agent, disodium hydrogen phosphate dodecahydrate, was added to molten CH 3 COONa·3H 2 O, and emulsified in an emulsifying device at a stirring speed of 5000 r / min for 0.5 h to obtain a mixture A.
[0127] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of disodium hydrogen phosphate dodecahydrate is 5.0 wt.%.
[0128] (3) Thickening treatment
[0129] At 70° C., xanthan gum was added to mixture C in 5 portions, with 2.0 g added each time. The mixture was stirred at a speed of 35 r / min and thickened for 1.5 h to obtain mixture B.
[0130] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of xanthan gum is 2.0 wt.%.
[0131] (4) First mixing process
[0132] At 70°C, 6 g of temperature regulator formamide was added to the molten mixture B for high temperature treatment at a stirring speed of 60 r / min for 2 h. Then, the temperature was adjusted to 30°C and low temperature treatment was performed for 2 h to obtain mixture C.
[0133] (5) Second mixing process
[0134] At 70°C, 0.5 g of mercaptobenzothiazole and a particle size of Dv 50 1.5 g of thermally conductive filler nickel foam with a particle size of 150 μm was added to the molten mixture C, with a stirring speed of 50 r / mi and an ultrasonic frequency of 55 kHz for 2 h to obtain a mixture D.
[0135] (6) Cooling treatment
[0136] The mixture D is cooled to room temperature 25° C., and the mixture D solidifies to form an inorganic salt phase change material.
[0137] Examples 1-2 to 1-7, Examples 1-10 to 1-15, and Comparative Examples 1-1 to 1-5 are the same as Example 1-1, except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, thermal conductive filler, thickener and corrosion inhibitor are adjusted in each processing step as shown in Table 1.
[0138] Example 1-8, except that the types and contents of inorganic hydrated salt, temperature regulator, nucleating agent, thermal conductive filler, thickener and corrosion inhibitor are adjusted as shown in Table 1 in each processing step, the preheating temperature in steps (1)-(3) and step (5) is selected to be 70°C according to the melting point of the inorganic hydrated salt, and the high temperature treatment temperature selected by adding the temperature regulator in step (4) is 65°C and the low temperature treatment temperature is 20°C, the rest is the same as Example 1-1.
[0139] In Example 1-9, except that the types and contents of the inorganic hydrated salt, temperature regulator, nucleating agent, thermal conductive filler, thickener and corrosion inhibitor are adjusted as shown in Table 1 in each processing step, the preheating temperature in steps (1)-(3) and step (5) is selected to be 70°C according to the melting point of the inorganic hydrated salt, and the high temperature treatment temperature selected for adding the temperature regulator in step (4) is 50°C and the low temperature treatment temperature is 10°C, the rest is the same as Example 1-2.
[0140] Example 1-16 is the same as Example 1-1 except that the types and contents of inorganic hydrated salt, temperature regulator, nucleating agent, thermal conductive filler, thickener and corrosion inhibitor are adjusted in each treatment step as shown in Table 1, and the high temperature treatment temperature selected for adding the temperature regulator in step (4) is 70°C and the low temperature treatment temperature is 20°C.
[0141] Example 1-17 is the same as Example 1-1 except that the types and contents of inorganic hydrated salt, temperature regulator, nucleating agent, thermal conductive filler, thickener and corrosion inhibitor are adjusted as shown in Table 1 in each treatment step, and the high temperature treatment temperature selected for adding the temperature regulator in step (4) is 75°C and the low temperature treatment temperature is 35°C.
[0142] The preparation parameters of Examples 1-1 to 1-17 and Comparative Examples 1-1 to 1-5 are shown in Table 1.
[0143] Table 1
[0144]
[0145]
[0146] The performance parameters of Examples 1-1 to 1-17 and Comparative Examples 1-1 to 1-4 are shown in Table 2.
[0147] Table 2
[0148]
[0149]
[0150] It can be seen from Examples 1-1 to 1-17 and Comparative Examples 1-1 to 1-5 in Tables 1 and 2 that by adding a temperature regulator to the inorganic salt phase change material composition and selecting the components of the inorganic salt phase change material composition within a suitable range, the phase change temperature of the obtained inorganic salt phase change material can be reduced, and the enthalpy decay rate, supercooling and energy storage density after 2000 cycles are all within a suitable range. The inorganic salt phase change material of the embodiments of the present application can be used in a heat pump system and can improve the energy efficiency ratio of the heat pump system.
[0151] It can be seen from Comparative Example 1-1 to Comparative Example 1-2 that when the added temperature regulator is 5wt.% to 8wt.%, the phase change temperature reduction rate, enthalpy decay rate after 2000 cycles, supercooling and energy storage density of the obtained inorganic phase change material are all within an appropriate range. When the weight percentage of the temperature regulator is lower than 5wt.%, the content of the temperature regulator is insufficient and the effect of lowering the temperature is limited. When the weight percentage of the temperature regulator is higher than 8wt.%, although the temperature regulator can significantly reduce the phase change temperature, it causes the supercooling of the inorganic salt phase change material to deteriorate.
[0152] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An inorganic salt phase change material composition, characterized in that: The composition comprises the following components: Inorganic hydrated salt 84.0wt.%~92.5wt.%, temperature regulator 5.5wt.%~8.0wt.%, nucleating agent 1.0wt.%~5.0wt.%, thickener 1.0wt.%~3wt.%; Wherein, the temperature regulator is selected from at least one of formamide, acetamide, urea and glycine, and the weight ratio of the inorganic hydrated salt to the temperature regulator is S, and the range of S is 10.40 to 13.
82.
2. The composition according to claim 1, characterized in that Based on the total weight of the composition, the composition comprises the following components: Inorganic hydrated salt 87.0wt.%~90.0wt.%, temperature regulator 6.0wt.%~7.0wt.%, nucleating agent 3.0wt.%~4.0wt.%, thickener 1.0wt.%~2.0wt.%.
3. The composition according to claim 1, characterized in that The inorganic hydrated salt is selected from at least one of magnesium nitrate hexahydrate, sodium thiosulfate pentahydrate, sodium acetate trihydrate, and calcium chloride hexahydrate; The nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium phosphate heptahydrate, sodium pyrophosphate, sodium dihydrogen phosphate, strontium chloride hexahydrate, kainite hexahydrate, calcium sulfate dihydrate, and expanded graphite; The thickener is selected from at least one of cyclodextrin, sodium alginate, carrageenan, pectin, sodium carboxymethyl cellulose, xanthan gum, gum arabic, and water-soluble starch.
4. The composition according to any one of claims 1 to 4, characterized in that The composition further comprises a corrosion inhibitor, and the weight percentage of the corrosion inhibitor is 0.2wt.% to 1.0wt.% based on the total weight of the composition; The corrosion inhibitor is selected from at least one of quaternary ammonium salt, benzotriazole, mercaptobenzimidazole and tungstate.
5. The composition according to any one of claims 1 to 4, characterized in that The composition further comprises a thermally conductive filler, wherein the weight percentage of the thermally conductive filler is 1.5 wt.% to 3.0 wt.% based on the total weight of the composition; The thermally conductive filler is selected from at least one of metal-organic frameworks, metal foams, expanded graphite, carbon nanotubes, boron nitride, molybdenum disulfide, aluminum oxide, magnesium oxide, and iron oxide.
6. A method for preparing an inorganic salt phase change material, characterized in that: include: The components of the inorganic salt phase change material composition according to any one of claims 1 to 6 are mixed.
7. The preparation method according to claim 6, characterized in that: Mixing the components of the inorganic salt phase change material composition comprises the following steps: The inorganic hydrated salt is heated to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt, and a preheating treatment is performed to obtain a molten inorganic hydrated salt; Adding the nucleating agent to the molten inorganic hydrated salt and performing emulsification treatment to obtain a mixture A; Adding the thickener to the mixture A to perform thickening treatment to obtain a mixture B; Adding the temperature regulator to the mixture B, performing a first mixing process, and obtaining a mixture C; adding the corrosion inhibitor and the thermal conductive filler to the mixture C, performing a second mixing process, and obtaining a mixture D; The mixture D is cooled and solidified to obtain an inorganic salt phase change material.
8. The composition according to claim 7, characterized in that The first mixing treatment at least includes high temperature treatment and low temperature treatment; The high temperature treatment at least includes: a stirring speed of 150 r / min to 200 r / min, a temperature of 65° C. to 75° C., and a time of 1.5 to 2.5 h; The low temperature treatment at least includes: a temperature of 20°C to 35°C and a time of 1h to 2h; The total time of the first mixing treatment is 2.5 h to 4.5 h.
9. The composition according to claim 7, characterized in that The preheating treatment at least includes: a time of 2 hours to 3 hours, and a preheating temperature higher than the melting point of the inorganic hydrated salt in a temperature range of 18° C. to 22° C.; The emulsification treatment at least includes: stirring at a speed of 5000 r / min to 6000 r / min for 25 min to 30 min; The thickening treatment at least comprises: adding the thickener to the blend in batches, with a stirring speed of 30 r / min to 50 r / min, for 2 h to 3 h, and the weight of the thickener added each time is 1.0% to 2.0% of the total weight of the thickener; The second mixing treatment at least includes: a stirring speed of 30 r / min to 50 r / min, an ultrasonic frequency of 50 kHz to 60 kHz, and a time of 1.5 h to 2 h.
10. An inorganic salt phase change material, characterized in that: The inorganic salt phase change material is prepared by the preparation method described in any one of claims 7 to 10.
11. A heat pump system, characterized in that: An energy storage unit is included, wherein the energy storage unit includes: An energy storage shell having an energy storage cavity therein; A heat exchange tube, disposed in the energy storage chamber; and The phase change layer comprises the inorganic salt phase change material according to claim 10, wherein the phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.